THEORETICAL FOUNDATIONS OF COMPETENCY INTERFERENCE IN COGNITIVE-NEURODIDACTIC-COMPETENCY-INTEGRATIVE EDUCATIONAL MODEL - Alimov Azam Anvarovich (Sciental Journals Publishing, 2025)
The integration of cognitive, neuropsychological, and competency-based approaches in the Cognitive-Neurodidactic-Competency-Integrative (CNCI) educational model presents significant challenges when phases and competencies are not properly aligned. This study analyzes competency interference phenomena that occur when universal human competencies (UHC), personal competencies (PC), general professional competencies (GPC), and professional competencies (PRC) are organized in a discordant manner. Through analysis of cognitive load theory (CLT), dual coding theory (DCT), and brain-based learning (BBL) frameworks, we identify four primary types of interference: functional, methodological, sequential, and load interference. Our findings demonstrate that cognitive phase misalignment, unmanaged cognitive loads, and contextual detachment significantly impair learning outcomes in engineering education. We propose systematic solutions including phase-based competency alignment, balanced cognitive load distribution, and interdisciplinary integration strategies. This research provides theoretical foundations and practical frameworks for optimizing competency-based curricula in technical education.
Keywords: Competency interference, CNCI model, cognitive load theory, engineering education, cognitive phases, competency-based learning.